On relaxed LMI-based designs for fuzzy regulators and fuzzy observers - Teixeira, MCM; Assuncao, E.; Avellar, R. G. (Institute of Electrical and Electronics Engineers (IEEE), 2003)
Relaxed conditions for stability of nonlinear, continuous and discrete-time systems given by fuzzy models are presented. A theoretical analysis shows that the proposed methods provide better or at least the same results of the methods presented in the literature. Numerical results exemplify this fact. These results are also used for fuzzy regulators and observers designs. The nonlinear systems are represented by fuzzy models proposed by Takagi and Sugeno. The stability analysis and the design of controllers are described by linear matrix inequalities, that can be solved efficiently using convex programming techniques. The specification of the decay rate, constrains on control input and output are also discussed.
Keywords: control of nonlinear systems; fuzzy control; linear matrix inequalities (LMIs); quadratic stability; Takagi and Sugeno (T-S) fuzzy model